Math, asked by Anonymous, 2 months ago

❐ Brainly Moderators
❐ Brainly Stars
❐ Brainly Best Users
 \\  \\

\huge\red{\bold{\underline{\underline{Question:-}}}}Prove that the equation, \large\rm{\sqrt{x+1}-\sqrt{x-1}\:=\:\sqrt{4x-1}} has no solution​

Answers

Answered by kamalhajare543
29

Answer:

Given:-

 \sf \sqrt{x + 1}  -  \sqrt{x + 1}  =  \sqrt{4x - 1}

 \sf \: x + 1 + x - 1 - 2 \sqrt{x + 1}  - \:  \sqrt{x - 1}  = 4x - 1

 \sf \:  - 2 \sqrt{x {}^{2} - 1 }  \:  \:  \: 2x - 1

 \sf \: 4x {}^{2}  - 4 = 4 {}^{2}   + 1 - 4x {}^{}

 \sf \: 4x =  - 5 =  > x =  -  \frac{5}{4}

 \sf \: But  \: of  \: x \:  = -   \frac{5}{4}  \sqrt{x + 1} , \sqrt{x - 1} , \:  \sqrt{4x - 1}

Are not Define

Therefore,No solution

Answered by MrImpeccable
21

ANSWER:

To Prove:

  • \rm{\sqrt{x+1}-\sqrt{x-1}=\sqrt{4x-1}}

Proof:

We are given that,

\implies\rm{\sqrt{x+1}-\sqrt{x-1}=\sqrt{4x-1}- - - - (1)}

Squaring both sides,

\implies\rm{(\sqrt{x+1}-\sqrt{x-1})^2=(\sqrt{4x-1})^2}

We know that,

\hookrightarrow (a-b)^2=a^2+b^2-2ab

So,

\implies\rm{(\sqrt{x+1}-\sqrt{x-1})^2=(\sqrt{4x-1})^2}

\implies\rm{(\sqrt{x+1})^2+(\sqrt{x-1})^2-2(\sqrt{x+1})(\sqrt{x-1})=4x-1}

\implies\rm{x+1\!\!\!/+x-1\!\!\!/-2\sqrt{(x+1)(x-1)}=4x-1}

We know that,

\hookrightarrow (a+b)(a-b)=(a)^2-(b)^2

So,

\implies\rm{2x-2\sqrt{(x+1)(x-1)}=4x-1}

\implies\rm{2x-2\sqrt{(x)^2-(1)^2}=4x-1}

\implies\rm{2x-2\sqrt{x^2-1}=4x-1}

Transposing 2x to RHS,

\implies\rm{-2\sqrt{x^2-1}=4x-1-2x}

\implies\rm{-2\sqrt{x^2-1}=2x-1}

\implies\rm{2\sqrt{x^2-1}=1-2x}

Squaring both sides,

\implies\rm{(2\sqrt{x^2-1})^2=(1-2x)^2}

\implies\rm{2^2(x^2-1)=(1)^2+(2x)^2-2(1)(2x)}

\implies\rm{4(x^2-1)=1+4x^2-4x}

\implies\rm{4x^2\!\!\!\!\!\!/\:-4=1+4x^2\!\!\!\!\!\!/\:-4x}

\implies\rm{-4=1-4x}

On rearranging,

\implies\rm{4x=1+4}

\implies\rm{4x=5}

\implies\rm{x=\dfrac{5}{4}}

Now, we will substitute this in (1),

\implies\rm{\sqrt{x+1}-\sqrt{x-1}=\sqrt{4x-1}}

\implies\rm{\sqrt{\dfrac{5}{4}+1}-\sqrt{\dfrac{5}{4}-1}=\sqrt{4\!\!\!/\left(\dfrac{5}{4\!\!\!/}\right)-1}}

\implies\rm{\sqrt{\dfrac{5+4}{4}}-\sqrt{\dfrac{5-4}{4}}=\sqrt{5-1}}

\implies\rm{\sqrt{\dfrac{9}{4}}-\sqrt{\dfrac{1}{4}}=\sqrt{4}}

\implies\rm{\dfrac{3}{2}-\dfrac{1}{2}=2}

\implies\rm{\dfrac{3-1}{2}=2}

\implies\rm{\dfrac{2}{2}=2}

\implies\rm{1=2}

As, LHS ≠ RHS, the value of x, is not valid.

Hence no solution exists.

HENCE PROVED.

Similar questions